2021
DOI: 10.1155/2021/3771866
|View full text |Cite
|
Sign up to set email alerts
|

CYP2J2 Is a Diagnostic and Prognostic Biomarker Associated with Immune Infiltration in Kidney Renal Clear Cell Carcinoma

Abstract: Cytochrome P450 family 2 subfamily J member 2 (CYP2J2), a member of the monooxygenase cytochrome P450 (CYP) family and the only member of the human CYP2J subfamily, has many functions, including regulation of oxidative stress, inflammation, apoptosis, and immune responses. However, its role in cancer development has not been clearly elucidated. In this study, expression levels of CYP2J2 in various cancer types were determined using the Oncomine, the Gene Expression Profiling Interactive Analysis (GEIPA), Drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Renal cell carcinoma (RCC) can be divided into different subtypes according to its histological characteristics with unique genetic and molecular alterations, different clinical processes and therapeutic responses (Linehan et al, 2010;Linehan and Ricketts, 2013;Moch et al, 2016). RCC is a tumor originating from renal epithelium (Sanchez-Gastaldo et al, 2017;Zou and Mo, 2021). The most common pathological subtype of RCC is kidney renal clear cell carcinoma (KIRC), accounting for about 75% of RCC (Linehan and Ricketts, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Renal cell carcinoma (RCC) can be divided into different subtypes according to its histological characteristics with unique genetic and molecular alterations, different clinical processes and therapeutic responses (Linehan et al, 2010;Linehan and Ricketts, 2013;Moch et al, 2016). RCC is a tumor originating from renal epithelium (Sanchez-Gastaldo et al, 2017;Zou and Mo, 2021). The most common pathological subtype of RCC is kidney renal clear cell carcinoma (KIRC), accounting for about 75% of RCC (Linehan and Ricketts, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The former studies identified that CYP2J2 expressions are particularly high in extrahepatic tissues, including the heart, pancreas, lung, kidney, brain, and skeletal muscle [ 36 , 37 ]. Especially, the recent study elucidated that CYP2J2 can be used as a biomarker in renal clear cell carcinoma [ 38 ]. The CYP2J2 are found to have strong and selective upregulated expressions in human tumor cells [ 39 ] and had a protective effect against ROS-induced cell deaths in adult ventricular myocytes and breast cancer MDA-MB-468 cells [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to analyze the clinicopathological features of KIRC patients according to the WHO classification and Tumor Node Metastasis (TNM) staging for selecting appropriate treatment methods [ 6 ]. However, there may be significant differences in prognosis even in patients with the same TNM staging and pathological grade after similar treatment [ 7 , 8 ], indicating that KIRC is a heterogeneous tumor, and the existing clinicopathological features and classification are not sufficient to evaluate the prognosis and risk stratification of KIRC patients. Therefore, finding a new method with high predictive value is of great significance to improve the prognosis of KIRC.…”
Section: Introductionmentioning
confidence: 99%